Ownership structure and firm performance - Zandi, G.; Jaspal, S. J. S. *; Shafi, M.; Syed, Ehsanullah (2020)
This study implies that diffuse ownership structure negatively affects firm performance. Our study based on empirical evidence found that the ownership structure (the outsider and the insider i.e. managerial ownership) favorably increase the firm performance. Our sample data was based on 200 Malaysian companies listed on the Malaysian stock exchange Bursa Malaysia. We used Tobin’s Q and accounting rate of return for firm performance measurement and compared it with important ownership structure and managerial ownership structure. Our results indicate that both ownership structures have a positive relationship with firm performanc